Yeast mediates the interspecific interaction between introduced Bactrocera dorsalis and indigenous Bactrocera minax - Ren, Xue‐Ming; Yang, Yi‐Shi; Guo, Ru‐Xin; Wang, Hao‐Ran; Qi, Xue‐Wei; Cao, Shuai; Lai, Yan‐Nan; Zhang, Gui‐Jian; Niu, Changying (Pest management science, 2023)
Background Host plant–microbe associations mediate interspecific interactions amongst herbivorous insects. However, this theory has rarely been ecologically verified in tephritid fruit flies. Research on this subject can not only help predict tephritid species invasion and occurrence patterns, but also develop potential novel lures for the control of the tephritid fruit fly pests. Recently, we observed mixed infestation of Bactrocera minax and Bactrocera dorsalis larvae in citrus orchards, which prompted us to explore the underlying mechanism. Results Following oviposition by B. minax, the yeast Pichia kluyveri translocated to and proliferated inside the citrus fruit. The level of d‐limonene released from citrus fruits containing P. kluyveri was 27 times higher than that released from healthy fruits. Mature B. dorsalis females were attracted to d‐limonene and oviposited into fruits previously infested by B. minax. Furthermore, the interspecific interaction between B. dorsalis and B. minax within the same fruit significantly decreased the number of surviving larvae and pupal weight in B. dorsalis, but its effect on B. minax was weaker. Conclusion In the studied interspecific interaction, B. minax occupies the dominant position, implying ecological significance for this species in terms of consolidating its own niche and inhibiting the invasion of exotic species. To our best knowledge, this is the first report from both ecological and physiological perspectives on a symbiotic yeast mediating the interaction between B. minax and B. dorsalis through altering fruit volatiles. © 2022 Society of Chemical Industry. Pichia kluyveri mediates the interaction between introduced Bactrocera dorsalis and indigenous Bactrocera minax through increasing the concentration of d‐limonene released from infested citrus fruits.